Soy Shake Enterprise / Muhammad Safuan Abdul Latip... [et. al] - Abdul Latip, Muhammad Safuan; Abdul Kadir, Mohamad Arif; Abu Bakar, Muhammad Hanif Omar; Tumin, Siti Aisyah; Othman, Nur Saffa Yusra (2012)
Soy Shake Enterprise is our company names that we planned to become the symbols and sign of proudness of our partnership that can satisfies our customer needs. Our company operation is sell a varieties type of soy shakes to all people around Melaka that fulfil their need and want and also give a full satisfaction of service. On the other hand, for this business for each partner needs to contribute RM 11 664.40 and it turns our capital for this business is RM58 322.00. This partnership business owned by Muhammad Haniff Omar Bin Abu Bakar, Muhammad Safuan Bin Abdul Latip, Mohamad Arif Bin Abdul Kadir, Sitl Aisyah BintiTumin, and Nur SaffaYusra Binti Othman. Our supplies that responsible to supply all the item such as fresh soy, condiment such as cincau, selasih seed, cendol, and com puree are around Melaka such as CSB Food Trading. There is no companies has sell this product and we are the first one that open this type of product to introduce to customer the Malay people product to market. Based on our competitive analysis, our business will successful soon. We hope our business can joy the customer starting age from child until adult and also can obtain our target to be a top 5 of successfully business of drinks that can customer remember in their mind which is Soy Shake!